Utilization of Service Oriented Architecture to Customize Accounting Business Process in Open ERP System for Smart SME’s - Muhardi Saputra; Sanny Putra Hendarsyah; Wahjoe Witjaksono (International Journal of Innovation in Enterprise System, 2020)
Small and medium enterprises or commonly referred to as SMEs in Indonesia are business activities that are in great demand after the economic crisis which resulted in the termination of employment (PHK) experienced by most companies. The role of SMEs in the Indonesian economy has now been recognized by the wider community. However, many SMEs in Indonesia are still running their business processes separately, especially in the accounting system, so that the business processes are running poorly, financial transactions that are still recorded and reported manually and separately, sales/purchase account items that are still recorded manually, and there's no system that supports the accounting process for SMEs.The output from this research is an Open Source ERP-based Smart SME system design in the accounting module by embedding the "smart" feature, namely analytic accounting. This design expected to be the standard and best practice in the SME accounting system so that SME's actors can create and get more structured financial reports and can design an integrated system that supports a real-time data management system.The research method used in this research uses the Service Oriented Architecture (SOA) approach. This method also refers to certain services on one platform such as services for making payments, transferring payments, and checking the status of a bank account in one application. In general, all the research processes carried out refer to the step by step of SOA and there must be input and output in designing the business model. This method is used to design business process models and services based on the accounting system problems experienced by SMEs.